Management of Pod Fly, Melanagromyza obtusa Malloch (Diptera: Agromyzidae) in Pigeonpea Varieties Sown Across Different Dates - Kannihalli, Saleemali; Rachappa, V.; Rathod, Pandit S.; Sushila, N.; Hanchinal, S. G. (International Journal of Economic Plants, 2024)
An experiment conducted during kharif, 2019–20 (July 2019–February 2020) at Zonal Agricultural Research Station, Kalaburagi, University of Agricultural Sciences, Raichur, Karnataka, India on the management of pod fly with recommended chemicals (Imidacloprid 17.8 SL 0.20 ml+jaggary 10 g l-1 as first spray at 10 days after pod formation and second spray with Thiamethoxam 25 WG 0.2 g+jaggary 10 g l-1 at 15 days after first spray) in pigeonpea varieties sown under different dates revealed, minimum pod damage (21.07%), seed damage (14.51%) and yield (1062.66 kg ha-1) in variety TS 3R. However, significantly higher pod damage, seed damage and yield of 31.47%, 24.89% and 1251.13 kg ha-1, respectively was found in variety BSMR 736. Among different sowing dates, the crop sown on 20th July recorded significantly least pod damage (21.07%) and seed damage (14.06%) compared to 20th August sown crop which recorded significantly higher pod damage of 32.13% and seed damage of 25.86%. Yield was significantly higher in 20th July sown crop (1295.89 kg ha-1) and it was lower in the crop sown on 20th August (1032.90 kg ha-1). With respect to management, minimum pod damage (17.07%) and seed damage (11.52%) was noticed in protected plots while it was maximum in unprotected plots with 35.02 and 26.62% pod and seed damage, respectively. The yield was significantly higher in protected plots (1242.37 kg ha-1) when compared to unprotected plots (1080.65 kg ha-1).